2002
DOI: 10.4049/jimmunol.168.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Contributions from Self-Renewal and Trafficking to the Uterine NK Cell Population of Early Pregnancy

Abstract: Uterine NK (uNK) cells are abundant in human and murine uteri during decidualization. It is unclear whether precursors of uNK (pre-uNK) cells self-renew or are recruited from other sites. To assess self-renewal of pre-uNK cells, uterine segments from NK cell-competent mice were grafted orthotopically into NK/uNK cell-deficient or wild-type mice. Only in wild-type recipients did decidualized grafts contain uNK cells, indicating that pre-uNK cells do not self-renew in uterus. To identify pre-uNK cell sources, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(145 citation statements)
references
References 49 publications
4
139
2
Order By: Relevance
“…Subsets of Lin Ϫ CD34 ϩ cells isolated from decidua also appear to express other markers associated with NK progenitor cells including integrin ␤7, and CD117 (data not shown). However, in mice, elegant cell transfer studies into NK cell-deficient animals suggested that dNK cell precursors were not present in uterine grafts, but could be found in secondary lymphoid tissues (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Subsets of Lin Ϫ CD34 ϩ cells isolated from decidua also appear to express other markers associated with NK progenitor cells including integrin ␤7, and CD117 (data not shown). However, in mice, elegant cell transfer studies into NK cell-deficient animals suggested that dNK cell precursors were not present in uterine grafts, but could be found in secondary lymphoid tissues (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…This donor had normal random and fasting blood glucose, insulin, and lipid profiles. Peripheral blood lymphocytes were isolated as previously described (24,29), adjusted to 5 ϫ 10 6 cells/l in serum-free RPMI and incubated with anti-CD56 mAb (1:100; Coulter Immunology, Hialeah, FL).…”
Section: Methodsmentioning
confidence: 99%
“…These changes are completed histologically in mice by midpregnancy (gestation day [gd] 10 of a 19-to 20-day term [23]). Transplantable uNK progenitor cells are not found in mouse uteri but occur in all peripheral lymphoid tissues (24). Although hematopoeitic stem cells occur in human uteri (25), in vitro assays show that human CD56 bright blood NK cells, the minor blood NK cell type, gain in functional interactions with endothelium of the decidua basalis at the preovulatory menstrual cycle surge in luteinizing hormone.…”
mentioning
confidence: 99%
“…Neither decidualized grafts nor decidualized host uterus differentiated uNK cells, strongly suggesting that most uNK cell progenitors are recruited from the circulation. 13 In that study and most studies reported prior to 1995, mouse uNK cells were recognized by their lymphoid shape and the reactivity of their cytoplasmic granules with periodic acid Schiff's (PAS) reagent, a histochemical stain for glycoproteins, especially mucin. 14 Over the past decade, most investigators of mouse uNK cells have switched to use of the lectin Dolichos biflorus agglutinin (DBA) which reacts with terminal N-acetyl-D-galactosamine, for uNK cell identification.…”
Section: Dbamentioning
confidence: 99%